The impact of the war in Ukraine in the stability of Kosovo and Bosnia and Herzegovina viewed by young political influencers - Poças, Fernando Miguel Carreira (2023)
Thirty years after the 1990s’s wars, the Western Balkans face a new challenge due to the potential impact of war in Ukraine in regional stability. In my research, I revisit the events and the reasons that led to the bloody dissolution of Tito’s Yugoslavia and seek to demonstrate how they relate to the dissolution of the USSR and Ukraine’s recent history. I considered two study cases: Bosnia and Herzegovina, due to a complex political structure issued of Dayton peace agreements and the fragile balance between the two entities, with Republika Srpska’s leadership’s threats of secession and pro-Russian drive, and the risk of split in the Federation; and Kosovo, unrecognised by the UN, with the normalisation process with Serbia in a deadlock. After contextualising their current situation, I focus on how their young politicians, activists and analysts see the risk of Ukraine war’s spilling over, and how they foresee the future of the region. Due to their regional influence, I also approached political influencers from Serbia, Albania, and Croatia. I explored the content of 22 interviews and social media posts from 70 individuals, by engaging with framing as a theoretical framework of analysis, and balkanism, occasionally. I concluded that young influencers leverage Ukraine to convey their political message locally. Despite considering it a real threat, the risk of conflict in the region is not proactively mentioned to their audience. The future is unequivocally linked to NATO and EU, by this order.